A simple method for immobilising the upper limb following groin or abdominal flaps for soft tissue defects in the hand - Kamath, Jagannath B.; Sahu, Chitta Ranjan; Joshua, Thangam Verghese (Indian Journal of Plastic Surgery, 2004)
Abdominal and groin flaps are the main workhorse for soft tissue defects in hand injuries. A simple and easy method is being described for immobilising the upper limb following abdominal and groin flaps for soft tissue defects of the hand using commonly available clavicular braces. This is devoid of all the problems of immobilisation using the common methods such as adhesive plasters and pin fixators and has its own advantages.
Keywords: Groin flap; Abdominal flap; Immobilisation